2021
DOI: 10.1111/1556-4029.14951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of manubriosternal joint fusion and second costal cartilage calcification: Are they useful for estimating advanced age groups?

Abstract: The objectives of this study were to evaluate the manubriosternal joint (MSJ) to estimate the minimum chronological age of complete fusion, and how changes in this joint influence age estimation. The study also focused on investigating the calcification patterns of the second costal cartilage (SCC), as they may be related to age. Between January and September 2020, individuals between 30 and 80 years of age, who underwent chest tomography at our institution, were listed by sex and divided into five groups acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In this study, the fusion of the manubrio-sternal junction occurs in all age groups after the age of 30 years in females and 36 years in males. Fusion at the manubrio-sternal junction can occur through primary or matrical fusion (not age-related) and secondary or sclerotic fusion (probably age-related) [ 10 , 12 , 17 , 18 ]. The primary cartilaginous joint between the manubrium and mesosternum can be obliterated during early life and this process is thought to be the cause of the matrical fusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the fusion of the manubrio-sternal junction occurs in all age groups after the age of 30 years in females and 36 years in males. Fusion at the manubrio-sternal junction can occur through primary or matrical fusion (not age-related) and secondary or sclerotic fusion (probably age-related) [ 10 , 12 , 17 , 18 ]. The primary cartilaginous joint between the manubrium and mesosternum can be obliterated during early life and this process is thought to be the cause of the matrical fusion.…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies found that the manubrio-sternal and sterno-xiphoidal junctions fused at different times. Studies in this regard have been carried out in the Chinese [ 11 ], Indian population [ 12 - 16 ], South African [ 17 ], Turkish [ 18 , 19 ], Egyptian [ 20 ], Spanish [ 21 ], Japanese [ 22 ] and mixed population (mainly British) [ 10 ]. For the Thai population, Monum et al [ 23 ] developed a model for age estimation in the Thai male population using radiological analysis of chest plate ossification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other parameters, in parallel with the degree of calcification, are being evaluated. Oktay et al [13] showed that the degree of manubriosternal joint degeneration and calcification in the second costal cartilage significantly increase with age, but its range is wide. As the authors themselves emphasized, their results might be used to support traditionally accepted age-estimation methods but not as independent indicators of specific age ranges [13].…”
Section: Age Estimationmentioning
confidence: 99%
“…Oktay et al [13] showed that the degree of manubriosternal joint degeneration and calcification in the second costal cartilage significantly increase with age, but its range is wide. As the authors themselves emphasized, their results might be used to support traditionally accepted age-estimation methods but not as independent indicators of specific age ranges [13]. Multislice-computed tomography (MSCT) of the sternal end of the first right rib provides some interesting information about osseous and calcic projections (OCP) occurrence in patients aged 15-30.…”
Section: Age Estimationmentioning
confidence: 99%